In vitro Effects of Biologically Active Vitamin D on Myogenesis: A Systematic Review - Alliband, Kathryn H.; Kozhevnikova, Sofia V.; Parr, Tim; Jethwa, Preeti H.; Brameld, John M. (Frontiers in Physiology, 2021)
Vitamin D (VD) deficiency is associated with muscle weakness. A reduction in the incidence of falls in the elderly following VD supplementation and identification of the VD receptor within muscle cells suggests a direct effect of VD on muscle, but little is known about the underlying mechanisms. Here we systematically searched the literature to identify effects of active VD (1,25(OH)2D3) on skeletal muscle myogenesis in vitro, with no restriction on year of publication. Eligibility was assessed by strict inclusion/exclusion criteria and agreed by two independent investigators. Twelve relevant pa-pers were identified using four different cell types (C2C12, primary mouse satellite cells, primary chick myoblasts and primary human myoblasts) and a range of myogenic markers (myoD, myogenin, creatine kinase, myosin heavy chain and myotube size). A clear inhibitory effect of 1,25(OH)2D3 on proliferation was reported, while the effects on the different stages of differentiation were less consistent probably due to variation in cell type, time points and doses of 1,25(OH)2D3 used. However myotube size was consistently increased by 1,25(OH)2D3. Overall, the evidence suggests that 1,25(OH)2D3 inhibits proliferation and promotes differentiation of myoblasts, but future studies should use time courses to gain a clearer understanding.